Urban Recreational Space Heat-Emotion Distribution and Matching Pattern Based on Machine Learning: A Case Study of Guangzhou City - Wang Fuyuan; Zhang Zhiyu; Xie Yuanjing; Yang Xinyi; Sun Miao (Redai dili)
Recreational spaces play a pivotal role in enhancing the quality of national life, fostering physical and mental health, and promoting social interaction. While previous research has predominantly examined the supply side of urban recreational spaces, there is a noticeable gap in the characterization of these spaces based on societal perceptions. Using Guangzhou as a case study, this study harnesses big data sourced from Ma Feng Wo and Ctrip. Based on machine learning techniques, it discerns recreational emotions and synergizes Geographic Information System (GIS) spatial analysis with heat-emotion matching analysis. This approach facilitates a nuanced and precise examination of the structural and experiential characteristics of urban recreational spaces from the perspective of social perception. The objective of this study is to offer informed references for the strategic planning and management of urban recreational spaces. The findings indicate that: (1) The distribution of recreational spaces in Guangzhou exhibits a "core agglomeration, edge dispersion" pattern, characterized by a "one core, multiple centers" configuration. Notably, the central urban region and its proximate suburbs—specifically, the Panyu, Baiyun, and Huangpu Districts—show a marked concentration in both the number and popularity of recreational spaces. In contrast, peripheral urban zones primarily feature government residences, premium ecological recreational spaces, and hot spring resources. These areas—including the Huadu, Conghua, and Zengcheng urban areas, Conghua District's hot spring town, and Paitan town—stand out as secondary hubs in terms of recreational space concentration and popularity. Moreover, recreational spaces situated along waterfronts and in areas with dense road networks tend to follow a "point-axis" distribution model, with a staggering 90.45% of these spaces located within a 1 km radius of the road network. (2) The overall approval rate of urban recreational spaces in Guangzhou is significantly high, evidenced by an average positive emotion ratio of 86.99%. However, there is a marked polarization in terms of popularity, manifesting as a "core-edge" decline in spatial distribution. Recreational spaces that evoke predominantly positive emotions are primarily located in the city center and are proximate to the administrative seats of the Panyu, Baiyun, Huangpu, and Nansha Districts. These areas also record a low ratio of negative emotions. In contrast, neutral and negative emotions are more prevalent in the commercial streets and pedestrian zones of the central city, as well as the suburbs of the Conghua, Huadu, and Zengcheng Districts. A considerable emphasis on "cost performance" is observed across all emotional categories related to Guangzhou's urban recreational spaces, indicating a widespread concern among tourists/residents regarding the balance between the costs of these spaces and their service quality. (3) The congruence between popularity and emotional response in Guangzhou's urban recreational spaces is suboptimal. Spatially, this disconnect can be categorized into three distinct types: the "polarized" pattern in the central city, the "experience enhancement" pattern in the Huadu, Panyu, Baiyun, and Conghua Districts, and the "insufficient supply" pattern in the Zengcheng, Huangpu, and Nansha Districts. These findings provide valuable insights for metropolitan areas aiming to refine the layout and management of recreational spaces. By understanding social demands and experiences, cities can craft a more optimized group perception of urban recreational spaces, thereby enhancing tourists' satisfaction and elevating the well-being of residents.